Hubungan antara Kreativitas Guru dalam Mengajar dan Keaktifan Siswa dengan Hasil Belajar IPAS Siswa Kelas IV SD - Vaella Silfa Soleha; Sri Sami Asih (Postgraduate, University of Mataram, 2025)
Teacher creativity in teaching and student activeness affect student IPAS (Natural and Social Sciences) learning outcomes. This study aims to examine the relationship between teacher creativity in teaching and student activeness with IPAS learning outcomes of fourth grade students of Gugus Wijaya Kusuma Ngaliyan District Semarang City. With a quantitative approach and the type of correlation research used, the research sample was obtained using Proportional Random Sampling technique namely 112 students. The research data were collected using a closed questionnaire for the variables of teacher creativity in teaching and student activeness, as well as documentation of student report cards for the variable of IPAS learning outcomes. The data were analyzed using descriptive statistical analysis, prerequisite tests, and hypothesis tests consisting of simple correlation, multiple correlation, F test, and coefficient of determination. The results showed that teacher creativity in teaching and student activeness with IPAS learning outcomes had a significant relationship with rcount of 0.665, Fcount of 43.125, and the contribution was 44.20%. Thus, it can be concluded that there is a positive and significant relationship between teacher creativity in teaching and student activeness with IPAS learning outcomes of fourth grade students of Gugus Wijaya Kusuma Ngaliyan District Semarang City.